The Effect of Perioperative Adverse Events on Long-Term Patient-Reported Outcomes After Lumbar Spine Surgery. (18th November 2021) - Ayling, Oliver G S; Ailon, Tamir; Street, John T; Dea, Nicolas; McIntosh, Greg; Abraham, Edward; Jacobs, W Bradly; Soroceanu, Alex; Johnson, Michael G; Paquet, Jerome; Rasoulinejad, Parham; Phan, Phillipe; et al.
Graphical Abstract: